EPISODE DEPRESI SEDANG DENGAN TREMOR FUNGSIONAL: LAPORAN KASUS DENGAN PENDEKATAN NEUROPSIKIATRI - Anindya Anindya; Anak Ayu Sri Wahyuni; Sri Yenni Trisnawati GS; I Komang Ana Mahardika (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Functional tremor is a form of Functional Neurological Disorder that often presents diagnostic challenges because it is not accompanied by clear structural or neurophysiological abnormalities. This condition is frequently associated with affective disorders, including depression with somatic symptoms, thus requiring an integrative neuropsychiatric approach. The purpose of this case report is to describe a case of functional tremor accompanied by a moderate depressive episode with somatic symptoms and to discuss it within a neuropsychiatric framework. The subject was a 24-year-old man who had experienced progressive tremor since adolescence, which worsened during activity and emotional stress and improved at rest. The patient also reported depressive symptoms including persistent sadness, anergia, sleep disturbances, concentration difficulties, and somatic complaints. Neurological examination revealed an arrhythmic tremor with variable amplitude and frequency that could be suppressed. Supporting examinations, including MRI, MRA, and Electroneuromyography (ENMG), were within normal limits. The management consisted of a combination of antidepressant pharmacotherapy, supportive psychotherapy, education regarding the functional nature of the symptoms, as well as relaxation exercises and stress management techniques. This approach focused on functional recovery, reduction of affective symptoms, and improvement of the patient’s understanding of the relationship between emotional states and motor manifestations. The key finding of this case is that improvement in tremor symptoms occurred in parallel with the improvement of depressive symptoms, supporting the presence of shared neuropsychiatric mechanisms involving emotional regulation, attention, and the perception of motor control. This case implies that an integrative neuropsychiatric approach is essential not only for establishing an accurate diagnosis but also for planning effective, function-oriented management for the patient’s overall recovery. ABSTRAK Tremor fungsional merupakan salah satu bentuk Functional Neurological Disorder yang sering menimbulkan tantangan diagnostik karena tidak disertai kelainan struktural atau neurofisiologis yang jelas. Kondisi ini kerap berasosiasi dengan gangguan afektif, termasuk depresi dengan gejala somatik, sehingga memerlukan pendekatan neuropsikiatri yang integratif. Tujuan laporan kasus ini adalah mendeskripsikan kejadian tremor fungsional yang disertai episode depresi sedang dengan gejala somatik serta membahasnya dalam kerangka pendekatan neuropsikiatri. Subjek penelitian adalah seorang laki-laki berusia 24 tahun dengan keluhan tremor progresif sejak remaja yang memberat saat aktivitas dan kondisi emosional serta membaik saat istirahat. Pasien juga mengalami gejala depresi berupa suasana perasaan sedih, anergia, gangguan tidur, gangguan konsentrasi, dan keluhan somatik. Pemeriksaan neurologis menunjukkan tremor aritmik dengan amplitudo dan frekuensi bervariasi serta dapat disupresi. Pemeriksaan penunjang, termasuk MRI, MRA, dan Electroneuromyography (ENMG), menunjukkan hasil dalam batas normal. Tatalaksana yang diberikan meliputi kombinasi farmakoterapi antidepresan, psikoterapi suportif, edukasi mengenai sifat fungsional gejala, serta latihan relaksasi dan manajemen stres. Pendekatan ini difokuskan pada pemulihan fungsi, pengurangan gejala afektif, serta peningkatan pemahaman pasien terhadap hubungan antara kondisi emosional dan manifestasi motorik. Temuan penting dari kasus ini menunjukkan bahwa perbaikan gejala tremor berjalan seiring dengan perbaikan kondisi depresi, menguatkan adanya keterkaitan mekanisme neuropsikiatri antara regulasi emosi, atensi, dan persepsi kendali gerakan. Kasus ini memberikan implikasi bahwa pendekatan neuropsikiatri yang integratif tidak hanya membantu dalam penegakan diagnosis yang tepat, tetapi juga efektif dalam perencanaan tatalaksana yang berorientasi pada pemulihan fungsi pasien secara menyeluruh.